PENGARUH INTELLECTUAL CAPITAL TERHADAP KINERJA KEUANGAN PERUSAHAAN DAN PENILAIAN PASAR DENGANCORPORATE GOVERNANCE SEBAGAI VARIABEL MODERASI - Citra Chairunissa; Raden Rosiyana Dewi (Jurnal Akuntansi Trisakti, 2015)
The  objective  of  the  emperical  study  is  to  examine  and  to analyze  1)  The Influence of Intellectual Capital to Financial Performance, 2 ) The Influence of Intellectual Capital to Market Value, 3) The Influence of Intellectual Capital to Financial Performance with Corporate Governance as an Moderating  4) The Influence of Intellectual Capital to Market Value with Corporate Governance as an  Moderating  Variable.  The sample of  this emperical  study is the company financing company that listed in the Indonesia Stock Exchange (IDX) 2010-2012.  This  research  uses  purposive  sampling  method. Data  analysis  techniques include  1)  Descriptive  statistics, 2)  Normality  Test, 3)  Classical  Test Assumptions : Multicollinearity and Heteroskidastity , 4) Regression Testing : Coefficient of Determination Test , F Test , danUji T. The results of this empirical study are 1) Intellectual Capital significant positive effect on the company 's financial  performance ,  2)  Intellectual  Capital significant  negative effect  on market valuation , 3) Intellectual Capital no significant effect on the financial performance of companies   with   moderated Corporate Governance, 4) Intellectual Capital  had  no  significant  effect  assessment  of  the  performance market with moderated Corporate Governance